Narrative comprehension skills in School-Age Autistic and Typically Developing Children - Parada Salazar, Soledad; Cuevas Miranda, Claudia; Mantiñan, Nancy; Cea Soto, Carolina; Oyarzo Cofré, Valentina; Urra Arriagada, Pamela (Revista de Investigación en Logopedia, 2026)
Narrative comprehension skills, especially inferential comprehension, are essential for reading development and academic learning. In autism, however, research has predominantly focused on narrative production, leaving the systematic study of comprehension—particularly in Spanish-speaking contexts—in the background. The present study aimed to describe and compare literal and inferential narrative comprehension skills in Spanish-speaking autistic children and their typically developing peers.Participants were 42 students aged between 6 years and 7 years 11 months: 9 autistic children with below-average structural language (ALB), 12 autistic children with structural language within the average range (ALM), and 21 typically developing children (TD), all from schools in the municipality of Santiago, Chile. An ad hoc instrument was designed to assess narrative comprehension, including literal and inferential questions based on an audiovisual narrative.Results showed that TD outperformed ALM in inferential and total comprehension, whereas ALB scored significantly lower than both groups in literal, inferential, and total comprehension. In inferential questions, differences between the autistic groups were concentrated in thought and evaluative inferences, with ALM performing better, while emotional inferences were challenging for both subgroups. These findings highlight the need to consider structural language level when assessing narrative comprehension in autism and to design culturally relevant instruments for this population.
Keywords: Narrative comprehension; narrative inferences; autism; narrative discourse